Indigenous Knowledge System and Sustainable Management of Rural Resources in a Floodplain Village of the Brahmaputra Valley, Assam - Sourav Saha (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The villages of the State Assam are endowed with diverse natural resources which fulfill the household needs of the villagers and also feed even the landless people. The life and livelihoods of the villagers are intrinsically and intimately related to the ecological settings, and as such villagers can be considered as the ecosystem people. These ecosystem people have been utilizing the resources without causing harm to the village ecological settings. They have also developed some kinds of peculiar resource management systems through their traditional knowledge and belief systems (TKBS) which can be thought, in the present context, as economically affordable to rural poor on the one hand and environmentally adaptive to the rural landscapes on the other. Thus, this study can be considered as significant as the use and management practices of natural resources done by the rural people help the rural development planners and policy makers in order to formulate sustainable resource utilization and management strategies. The present study is, therefore, an attempt to investigate the status, diversity, utility and management systems of natural resources of a village, called Jatiabhangra in Kamrup district, Assam. The study is solely based on the primary data and information obtained through household questionnaire survey, field observation and oral interviews among the aged people of the village.